1987
DOI: 10.1098/rspa.1987.0043
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of surface-reaction segregation in cyclohexene hydrogenation and dehydrogenation over supported platinum

Abstract: The hydrogenation and dehydrogenation of cyclohexene has been studied in temperature-programmed and isothermal modes over oxide-supported Pt surfaces. The ratio of the rates of dehydrogenation: hydrogenation measured experimentally does not appear to correlate with that expected from standard thermodynamic free energies of formation. This modifi­cation of normal descriptions of catalysis could occur if reaction products separate and segregate on the Pt surface. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In early works, the dehydrogenation of cyclohexene was intensively studied in the absence of oxygen, with emphasis on the adsorption mechanism and kinetics depending on the nature of the catalysts, , and special attention was paid to precious metals as active sites. Adsorption and reaction studies on Pt (111) surface by Gland et al . showed that the dehydrogenation of cyclohexene intermediate is kinetically limited during the dehydrogenation of cyclohexane under 150 °C, whereas the dehydrogenation of cyclohexadiene intermediate to benzene occurs rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early works, the dehydrogenation of cyclohexene was intensively studied in the absence of oxygen, with emphasis on the adsorption mechanism and kinetics depending on the nature of the catalysts, , and special attention was paid to precious metals as active sites. Adsorption and reaction studies on Pt (111) surface by Gland et al . showed that the dehydrogenation of cyclohexene intermediate is kinetically limited during the dehydrogenation of cyclohexane under 150 °C, whereas the dehydrogenation of cyclohexadiene intermediate to benzene occurs rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In early works, the dehydrogenation of cyclohexene was intensively studied in the absence of oxygen, with emphasis on the adsorption mechanism and kinetics depending on the nature of the catalysts, 9 , 10 and special attention was paid to precious metals as active sites. 11 18 Adsorption and reaction studies on Pt (111) surface by Gland et al.…”
Section: Introductionmentioning
confidence: 99%